An Ontology-based Multi-agent Architecture for Distributed Health-care Information Systems - Falasconi, S.; Lanzola, G.; Stefanelli, M. (Methods of Information in Medicine, 1997)
Managing patients in a shared-care context is a knowledge-intensive activity. To support cooperative work in medical care, computer technology should both augment the capabilities of individual specialists and enhance their ability of interacting with each other and with computational resources. Thus, a major shift is needed from centralized first generation health-care information systems to distributed environments composed of several interconnected agents, cooperating in maintaining a full track of the patient clinical history and supporting health-care providers in all the phases of the patient-management process. This paper outlines a general methodology to make architectural choices while designing or integrating new software components into a distributed health-care information system. A particular stress is laid on the specification of shared conceptual models, or ontologies, providing agents committing to them with the common semantic foundation required for effective interoperation.
Keywords: Agents; Ontology; Distributed Health-care